Literacy and learning lessons from a longtime teacher - Routman, Regie (Newark, Del. : International Reading Association, 2012)
What are the exemplary qualities, practices, and actions that lead to high reading and writing achievement for all learners? Veteran teacher, leader, and author Regie Routman has written a practical and inspirational guidebook for today's K-12 educators. Whether you are an experienced teacher, principal, or coach, or are just starting out, you will find the 100 literacy and learning lessons an invaluable resource for energizing your teaching and learning and raising achievement and enjoyment. The multitude of explicit strategies and useful ideas will lead to highly effective instruction and assessment in diverse classrooms and schools
Includes bibliographical references (p. 165-166) and index.
Keywords: Effective teaching; Language arts; Motivation in education